FILOSOFI KEPEMIMPINAN DAN KEPRIBADIAN - Kusnadi; Subhan; Insan Kamil; Ahmad Zainullah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Leadership and personality are two concepts that are interrelated and influence each other. A person's personality can affect their leadership style, and a person's leadership style can also affect their personality. This research aims to discuss the Philosophy of Leadership and Personality by using the literature research method. The results of this study discuss the relationship between leadership and individual personality. A person's personality is influenced by genetics, environment, life experiences, and social interactions, and personality concepts such as character, temperament, traits, types, and habits are interrelated and influence each other. In addition, there are various types of leadership such as authoritarian, paternalistic, charismatic, democratic, and militaristic. Leadership itself is the process of motivating others to achieve predetermined goals. This research also discusses the definition of personality from various schools of psychology such as psychoanalysis, behaviorism, cognitive psychology, humanism, and neuroscience. Further research can be done to explore how these factors influence the formation of personality and how this can affect one's ability to lead.